Prospective Analysis of Strategy for Developing Local Salak Production in Bilaporah Village, Madura Island - Anita Qur'ania; Soemarno Soemarno; Aminudin Afandhi (The Indonesian Green Technology Journal, 2018)
Bilaporah village is one of the largest local salak production areas in Bangkalan Regency, Madura, with a high productivity of 0.33 quintals per plant per year. However, these conditions are not matched by the quality of fruit produced and marketed. One of the quality problems of local salak fruit in Bilaporah is the less sweet taste of the fruit. The fruit quality such as taste in salak is strongly influenced by the cultivation practices applied by farmers. The cultivation practices in the local salak farms in Bilaporah have been analyzed to determine the sustainability of the local salak farms. The purpose of this study was to develop a strategic direction in the context of developing local salak production areas based on prospective analysis. Based on the results of the analysis, the improvement of the sustainability status of the local salak farms in Bilaporah through improving the quality of human resources is good for the main actors, namely farmers and government agencies, especially the Department of Agriculture of Bangkalan Regency.Keywords: Bilaporah village, Local salak, Prospective analysis, Sustainability